2020
DOI: 10.3389/frvir.2020.00010
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Down-Weighting in Visual-Postural Coupling Is Linked With Lower Cybersickness

Abstract: Sensory dynamics can be reshaped by environmental interaction, allowing adaptation to altered or unfamiliar conditions that would otherwise provoke challenges for the central nervous system. One such condition occurs in virtual reality, where sensory conflict is thought to induce cybersickness. Although the sensory re-weighting process is likely to underlie adaptation to cybersickness, evidence of a link between sensory re-weighting dynamics and cybersickness is rare. Here, we characterize the relationship bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 60 publications
(90 reference statements)
2
15
1
Order By: Relevance
“…In the present study, mismatch between visual cues and other sensory channels may have induced an evolution toward a less visually dependent multisensory integration and thus a shift toward FI. This interpretation is in line with the suggested prevalence of visual incoherence in cybersickness (LaViola, 2000;Bos et al, 2008;Shafer et al, 2017) and with other recent discussions on the role of sensory re-weighting (Mahboobin et al, 2005;Pavlou et al, 2011;Scotto Di Cesare et al, 2015;Weech et al, 2020). It seems important to note that sensory re-weighting is also often associated with postural adjustments (Weech et al, 2020), which is very interesting considering the theory of motion sickness for which postural instability precedes the emergence of symptoms (Stoffregen and Smart, 1998).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…In the present study, mismatch between visual cues and other sensory channels may have induced an evolution toward a less visually dependent multisensory integration and thus a shift toward FI. This interpretation is in line with the suggested prevalence of visual incoherence in cybersickness (LaViola, 2000;Bos et al, 2008;Shafer et al, 2017) and with other recent discussions on the role of sensory re-weighting (Mahboobin et al, 2005;Pavlou et al, 2011;Scotto Di Cesare et al, 2015;Weech et al, 2020). It seems important to note that sensory re-weighting is also often associated with postural adjustments (Weech et al, 2020), which is very interesting considering the theory of motion sickness for which postural instability precedes the emergence of symptoms (Stoffregen and Smart, 1998).…”
Section: Discussionsupporting
confidence: 82%
“…Based on this, we propose that the FDI flexibility observed here results from sensory re-weighting (i.e., adaptative response) in order to cope with a poor subjective experience of VR. Indeed, considering the solid literature discussing the links between perceptive mismatch and motion sickness (Reason and Brand, 1975;Oman, 1990;Rebenitsch and Owen, 2016), between perceptive mismatch and sensory re-weighting (Bray et al, 2004;Oman and Cullen, 2014;Mahboobin et al, 2005;Weech et al, 2018Weech et al, ,2020 and between FDI and perceptive mismatch (Kennedy, 1975;Cian et al, 2011), it seems coherent to interpret the shift toward FI as a sensory re-weighting compensatory mechanism. According to this view, internal models, in a situation of perceptive mismatch, might trigger a change of FDI (i.e., perceptive style) in order to cope with sensory incongruence, notably by reducing the processing and weight of problematic cues.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the multisensory integration theory, the weighting of visual cue might increase due to the unreliable of vestibular cue during passive motion stimulation (Angelaki et al, 2011 ; Carriot et al, 2015 ). As decreasing visual weighting relative to vestibular seems to be protective against virtual reality MS in physically stationary individuals when viewing unreliable and compelling visual scene, it is reasonable to speculate that increasing visual weighting to achieve visual-vestibular re-balance might help to counteract classical MS induced by unreliable vestibular cue of passive movement in the absence of corresponding visual input (Hettinger and Riccio, 1992 ; Weech et al, 2020 ). Based on this evidence, our results strongly suggested that providing stroboscopic light that provides visual cues relevant for motion pattern of the body might attenuate MS possibly via reducing brain prediction error when visual weighting is increased during passive motion stimulation.…”
Section: Discussionmentioning
confidence: 99%